Adjustment Costs and Capital Asset Pricing - Huffman, Gregory W. (Journal of Finance, 1985)
Discrete-time models of asset pricing have hitherto generally avoided studying the relationship between the underlying technology inherent in the economy and the determinants of the price of capital. A fully articulated economy is constructed in which there is a nontrivial technology for producing capital. The existence of adjustment costs in augmenting the quantity of capital has interesting implications for the stochastic properties of asset prices, as well as other macroeconomic variables. Examples of such economies are used to illustrate this point.